Kurikulum Pendidikan Versi Amtsal al-Qur’an - Hendro Juwono (Lembaga Penelitian dan Pengabdian Masyarakat STI. Blambangan Banyuwangi, 2020)
Abstract The content of the Al-Qur'an does not only contain educational teachings such as morals, rules and regulations, and stories, the Qur'an also inspires the discovery of educational concepts, including the concept of curriculum in education. Studies of the Qur'an from various aspects have been carried out by traditional and modern scholars. The study gave birth to educational concepts that are used today. By relying on the verses of the Koran, it examines important parts in education, such as the vision and mission of education in the perspective of the Koran, the purpose of education in the perspective of the Koran, and educational techniques that include role models , advice, punishment, stories, habits etc. Since the beginning of the Al-Qur'an has given serious attention about life, in particular the Al-Qur'an is a guide and guide to life to be a good human being and provision to be a kholifah. To achieve this al-Qur'an has formulated education with various aspects. In the Koran there is an educational term that can be used to formulate the teaching and learning process in accordance with the material taught and provided to students, namely students with various privileges and their respective differences, concrete examples from the formulation (curriculum) education in the Koran has been explored in depth in the discussion and results section.